Gender differences in endurance performance by elite cross-country skiers are influenced by the contribution from poling - Sandbakk, O.; Ettema, G.; Holmberg, H. C. (Scandinavian Journal of Medicine & Science in Sports, 2014)
Greater gender differences have been found in exercise modes where the upper body is involved. Therefore, the present study investigated the influence of poling on gender differences in endurance performance by elite cross-country skiers. Initially, the performance of eight male and eight female sprint skiers was compared during four different types of exercise involving different degrees of poling: double poling (DP), G3 skating, and diagonal stride (DIA) techniques during treadmill roller skiing, and treadmill running (RUN). Thereafter, DP was examined for physiological and kinematic parameters. The relative gender differences associated with the DP, G3, DIA and RUN performances were approximately 20%, 17%, 14%, and 12%, respectively. Thus, the type of exercise exerted an overall effect on the relative gender differences (P < 0.05). In connection with DP, the men achieved 63%, 16%, and 8% higher VO2peak than the women in absolute terms and with normalization for total and fat-free body mass (all P < 0.05). The DP VO2peak in percentage of VO2max in RUN was higher in men (P < 0.05). The gender difference in DP peak cycle length was 23% (P < 0.05). In conclusion, the present investigation demonstrates that the gender difference in performance by elite sprint skiers is enhanced when the contribution from poling increases.